The impact of brand awareness, brand image, and brand trust on consumer purchase decisions: Emphasizing awareness and trust as key drivers - Fadillah, Alpha Deepny; Triatmanto, Boge (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: In this modern era, the rapid and continuously increasing technological advancements each year have led to increasingly fierce business competition, especially in the gadget retail industry. The tendency of customers to consider both products and brands simultaneously when making purchasing decisions increasingly emphasizes the importance of understanding the factors that influence consumer behavior. Therefore, this study aims to analyze the influence of brand awareness, brand image, and brand trust on purchasing decisions at Tiga Putra Kawi Malang City, in order to provide useful insights for the company in formulating more effective marketing strategies. Methods: This study uses a quantitative method with a survey approach, involving 100 respondents who have shopped at Tiga Putra Kawi Malang City. Data were collected through questionnaires and analyzed using multiple linear regression to test the proposed hypotheses. Findings: The research findings indicate that brand awareness and brand trust have a positive and significant impact on purchasing decisions, while brand image does not have a positive and significant impact. This indicates that brand image is very important to customers. However, in this study, the level of customer awareness and trust in the brand has a greater influence on consumer purchasing decisions. Conclusion: The company needs to place more attention on efforts to increase consumer awareness and trust in the brand to encourage better purchasing decisions. On the other hand, methods for improving brand reputation need to be further evaluated. Novelty/Originality of this article: This study highlights that in the gadget retail industry, brand awareness and brand trust have a stronger influence on consumer purchasing decisions than brand image, offering new insights for marketing strategies.